Reaksi Pasar Saham terhadap Tarif Resiprokal Amerika Serikat: Studi Peristiwa pada BRICS dan Ekonomi Mitra - Rafdi Luthfan Farizi; Abdur Rafik (Universitas KH. Abdul Chalim Mojokerto, 2026)
Trade-policy announcements provide a natural experiment to examine how global policy uncertainty is transmitted into emerging equity markets. This study investigates the market reaction surrounding the U.S. reciprocal tariff announcement in early April 2025 by assessing three adjustment channels risk (volatility), price (abnormal returns), and trading activity (abnormal volume) across BRICS and selected partner markets. Using an event-study design, volatility is measured via standard deviation and tested using an F-test for differences in variance, while abnormal returns and abnormal volume are evaluated through OLS dummy regressions comparing event and post-event periods against the pre-event baseline. The results reveal heterogeneous and asymmetric responses across markets: some indices exhibit a pronounced shift in volatility and return dynamics, while trading activity responses are weaker or delayed. The findings highlight that trade-policy shocks are transmitted asymmetrically across emerging markets, with risk and price channels reacting faster than trading activity, challenging the assumption of uniform market adjustment under global policy uncertainty. These insights extend the literature on policy-induced financial spillovers by emphasizing a multi-channel adjustment mechanism and offer practical implications for portfolio risk management and market surveillance during periods of heightened policy uncertainty.